PENINGKATAN SIKAP ASSERTIF MELALUI TEKNIK ASSERTIF SISWA SMP ISLAM ATHIRAH BUKIT BARUGA MAKASSAR - Ayu Wahyuni Mustamin; Abdul Saman; Saniasa Saniasa (Universitas Negeri Makassar, 2021)
This study aims to find out the use of assertive techniques in increasing students' assertiveness through group counseling services, group counseling services include four stages, namely the Formation Stage, Transition Stage, Core Stage and Termination. This technique helps students pass through three main stages, namely the pre-counseling stage, counseling and post-counseling. The results of the research from assertive techniques are very effective. The results of this study indicate that the factual condition of students' assertiveness after participating in the Assertive Training process has experienced a significant increase, which is indicated by students being able to respect the rights of themselves and others, dare to express opinions in advance. In general, at the time of learning and in association, honest with oneself and others, able to determine attitudes by paying attention to the surrounding situation and conditions.